Biophysical impact of sphingosine and other abnormal lipid accumulation in Niemann-Pick disease type C cell models - Carreira, Ana C; Pokorna, Sarka; Ventura, Ana E; Walker, Mathew W; Futerman, Anthony H; Lloyd-Evans, Emyr; de Almeida, Rodrigo F M; Silva, Liana C (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2021)
Niemann-Pick disease type C (NPC) is a complex and rare pathology, which is mainly associated to mutations in the NPC1 gene. This disease is phenotypically characterized by the abnormal accumulation of multiple lipid species in the acidic compartments of the cell. Due to the complexity of stored material, a clear molecular mechanism explaining NPC pathophysiology is still not established. Abnormal sphingosine accumulation was suggested as the primary factor involved in the development of NPC, followed by the accumulation of other lipid species. To provide additional mechanistic insight into the role of sphingosine in NPC development, fluorescence spectroscopy and microscopy were used to study the biophysical properties of biological membranes using different cellular models of NPC. Addition of sphingosine to healthy CHO-K1 cells, in conditions where other lipid species are not yet accumulated, caused a rapid decrease in plasma membrane and lysosome membrane fluidity, suggesting a direct effect of sphingosine rather than a downstream event. Changes in membrane fluidity caused by addition of sphingosine were partially sustained upon impaired trafficking and metabolization of cholesterol in these cells, and could recapitulate the decrease in membrane fluidity observed in NPC1 null Chinese Hamster Ovary (CHO) cells (CHO-M12) and in cells with pharmacologically induced NPC phenotype (treated with U18666A). In summary, these results show for the first time that the fluidity of the membranes is altered in models of NPC and that these changes are in part caused by sphingosine, supporting the role of this lipid in the pathophysiology of NPC.
Keywords: Animals; cholesterol; Lysosomes; Phenotype; Sphingolipids; CHO buňky; lyzozomy; Niemann-Pick Disease, Type C; sfingosin; Cricetulus; sfingolipidy; Cholesterol; Endosomes; CHO Cells; fenotyp; zvířata; Sphingosine; buněčná membrána; endozomy; Niemannova-Pickova nemoc typu C; Cell Membrane